The distribution and functioning of rhizosheaths among South African grass species - Bailey, Catherine Lara (My University, 2016)
Rhizosheaths are sandy coatings covering ~ ~ entire length of the roots of many grass species~ .: They consLab of a mass of sand and silica particles en4?eddedin a mucilaginous layer and are matted togethel.· by a meahwozk of prolific epidermal had.ns, A study of the phenomenon of zhd aosheat.ha in South African grasses was undertaken. Aspects which were invest.igated include the occurrence of rhizosheaths amongSouth African grasses and the influence of environmental ccndftions on th.e presenc~ and , extent of rhizosheath development. In addition, information was ~fsll!led on their possible functions in terms of their contribution (s ) to plant vigour, through their influence on (1 nutrient and water uptake, particularly in low nutrient soil~ in '~\ ;'';-''>"\\ arid areas. An extensive surv,sy of herbal:"iul!lspecimens was conducted at the .. National Herbarium in Pretoria. It Wasfound that the presence" of rhizosheaths is a genetically fixed trait, occurring in the majority of gra~s species in south Africa. The extent to which sheaths develop (the thickness of the sheat.h and the degree 'to which the soil particles are bound to the sheath), varies between, and sometimes wi thin;) species. ~< Ii' Seeds of three sheath forming grass spccf.es which occur in South Africa, Anthephora pubescens Nees, Digitaria exientib« Steud and Eragrostis pallens Hade, were gr.ownundez different condi.t.Lona of soil texture and different conditions of water and nutrient (nitrogen (N') and phosphorus: (P) aVailability. Sheath development was found to be more extensive the higher the sand (relative/.: to clay) content in the soil. In addition, rhizoFlheaths developed to a greater extent in sandy soil with high watsr and nutrient availabilityu Therefore, the extent to whi;chsheaths develop is a facultative response directly to sandy soil, rather than toe resulting lower water and nutrient availability in this snil. A:fter \: Jtudying a number of physiological and morphological factors of the indiv~dua.ls in the different water and uutrient treatments it appeared that rhizosheaths compensate",dfor low water availability. In additionq sheaths appeared to «compensate -. I.' for low N availability when this 101;1T availability was a result of low soil water contentc The influence of sheath thickness on immobile nutrient ion uptake was investigated.. 'l'his was achieved by stimulating withinspeoies variation in sheath thiokness and mea.suring the difference in P uptake. The individuals with thick sheaths extracted more p from the. soil, and ~rom a greater volume of soil, than individuals with thin sheaths. This was particularly evident in conditi.ons of low P availabili,;ty i thereby highlighting , the important influence of thick rhizoshea,ths in soils with a low """" p status. The microbial biomass (as indicat;ed by t.he microbial Nand carbon concentrations) in the sheath soil was compared to that in the l?}y_k soil and the rliizosphe:r.e/out.er ,rhizosphere soil of r{ tinsheathed/sheathep, roots. Fromthi~ study it w~s concluded that rhj..zosheaths influence the"mic;:roorganisms in the soil ~djacent, \, to the root surface, since the l.hizosheath I')oil had a sigl,.ificantly higher microbial biomass than the soil .1:romthe other regions. " Fron\.the study it was concluded that the pzeaence of rhj.z6sheaths :maybe a mechanismemployed byce~tain grass species in order to enhance their ability to t.olera,te dry soil, which has J.owNand P availability. This mechanismmaybe a. sUbstitute for increased root production and root branching as well a~ increased mycorrhizal associations in plants in arid, low nutrient status soils~
A dissertation submitted to the Facult:y of Science, University of the Witwatersrand, Johannesburg, for the degree of Master of Science, Johannesburg 1994
Keywords: Grasses--South Africa